2022
DOI: 10.3390/polym14122314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Dosages of TESPT on Metal Friction and Metal Wear in the Mixing Process

Abstract: Studies show that the dispersion of silica in the mixing process is an important factor affecting the wear of the mixing chamber. As the most important mixing equipment, the long operational life of the internal mixer will cause wear in the rotor and chamber of the internal mixer. This wear increases the gap between the rotor and chamber of the internal mixer, reduces the mixing performance, weakens the dispersion of packing, and adversely affects the quality of the rubber produced. Therefore, it is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…During the plasticizing process, the cooling water temperature was set to 40–50 °C. Finally, the steps of the process were as follows: rubber breaking 4 times (roller distance 4 mm) 10 times thin (roller distance 0.5 mm) 2 times (roller distance 3 mm) [ 16 , 17 , 18 , 19 , 20 , 21 ] .…”
Section: Methodsmentioning
confidence: 99%
“…During the plasticizing process, the cooling water temperature was set to 40–50 °C. Finally, the steps of the process were as follows: rubber breaking 4 times (roller distance 4 mm) 10 times thin (roller distance 0.5 mm) 2 times (roller distance 3 mm) [ 16 , 17 , 18 , 19 , 20 , 21 ] .…”
Section: Methodsmentioning
confidence: 99%
“…TESPT is unstable undercutting or high-temperature conditions and results in a sulfur donor effect. 17 Rattanasom et al 18 reported that the optimum loading of CB/silica hybrid filler can improve the mechanical properties of NR-cured rubber. In this study, the mixtures were prepared by mixing the melt and the total amount of the filler was kept constant at 50 phr.…”
Section: Introductionmentioning
confidence: 99%
“…The most common silane agent is TESPT or Si69. TESPT is unstable undercutting or high‐temperature conditions and results in a sulfur donor effect 17 …”
Section: Introductionmentioning
confidence: 99%
“…The composites obtained by adding glass fibers have excellent properties. It has been reported that the composite material of glass fiber and rubber has good comprehensive properties and can improve its anti-skid performance [ 1 , 2 , 3 , 4 , 5 ]. As it is widely used in many fields, glass fiber is increasingly valued.…”
Section: Introductionmentioning
confidence: 99%